The Correlation Between Dietary Patterns and Physical Activity with Body Mass Index Among Faculty of Medicine UKI Students Class of 2022 in 2024 - Sihombing, Jumaini Andriana; Shakina Maharani, Maria Elizabeth; Hendrika, Wendy (Rifa'Institute, 2026)
Introduction: Dietary patterns and physical activity levels are critical determinants of health. UNICEF reports show a significant increase in processed food and fat consumption among Indonesian adolescents. Additionally, physical activity levels remain low, often falling below 90 minutes per week. These factors directly influence body composition as measured by Body Mass Index (BMI). Objective: This study aims to analyze the relationship between dietary patterns, physical activity, and BMI among medical students at Universitas Kristen Indonesia, batch of 2022. Method: This research used an analytical observational design with a cross-sectional approach. The study involved a sample of 112 participants. Data were collected using dietary pattern questionnaires and the Global Physical Activity Questionnaire. Result and Discussion: The bivariate analysis using the chi-square test yielded a p-value of 0.697 for the relationship between dietary patterns and BMI, indicating no significant correlation. However, the analysis of physical activity showed a significant relationship with BMI, with a p-value of 0.000. These results suggest that physical movement has a more immediate impact on BMI than dietary habits in this specific population. Conclusions: Physical activity significantly correlates with BMI among the studied students, while dietary patterns do not show a statistically significant association.